2010
DOI: 10.1017/s1368980010000078
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition knowledge, attitudes, behaviours and the influencing factors among non-parent caregivers of rural left-behind children under 7 years old in China

Abstract: Objective: To explore and compare nutrition knowledge, attitudes and behaviours (KAB) between non-parent and parent caregivers of children under 7 years old in Chinese rural areas, and to identify the factors influencing their nutrition KAB. Design: Face-to-face interviews were carried out with 1691 non-parent caregivers and 1670 parent caregivers in the selected study areas; multivariate logistic regression models were used to identify the factors influencing nutrition KAB in caregivers. Results: The awarenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…425 These could imply that the parent generation may have a different, but not necessarily better 426 understanding of healthy eating for children, compared to the grandparent generation. This is 427 inconsistent with previous studies suggesting that grandparents who cared for LBC had 428 poorer nutritional knowledge and attitudes than the children's parents (Tan et al, 2010), and 429 that they may not be able to provide a proper diet for LBC (Ye & Pan, 2011). 430 Our findings suggested that financial remittances from migrant parents were described 431 by grandparents as an important source for being able to include higher cost foodstuffs such It is important to take into account caregivers' experiences and intergenerational effects when 461 exploring LBC's health and well-being in rural China.…”
mentioning
confidence: 79%
“…425 These could imply that the parent generation may have a different, but not necessarily better 426 understanding of healthy eating for children, compared to the grandparent generation. This is 427 inconsistent with previous studies suggesting that grandparents who cared for LBC had 428 poorer nutritional knowledge and attitudes than the children's parents (Tan et al, 2010), and 429 that they may not be able to provide a proper diet for LBC (Ye & Pan, 2011). 430 Our findings suggested that financial remittances from migrant parents were described 431 by grandparents as an important source for being able to include higher cost foodstuffs such It is important to take into account caregivers' experiences and intergenerational effects when 461 exploring LBC's health and well-being in rural China.…”
mentioning
confidence: 79%
“…Likewise, Williams et al [24] found no significant correlation between maternal nutrition knowledge and children’s dietary outcomes. On the contrary, Tan et al [25] found that the awareness rate of nutrition knowledge was higher in the parent group compared to non-parent group as parents care more about their nutrition knowledge in order to improve their children’s nutritional status. Moreover, Kakinami et al [26] found that greater parental nutrition knowledge was associated with lower body mass index and other health related outcomes among children.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings can be found in other studies. For example, Tan et al (2010) selected one northern and six southern provinces that have a considerable number of children left behind, and compared parent caregivers and non-parent caregivers of children under seven years old. They found that non-parent caregivers had relatively poor nutrition knowledge, attitudes and behaviours.…”
Section: The Needs Of Children Left Behind In Rural Chinamentioning
confidence: 99%